The Art of Coding: The Language of Drawing, Graphics, and Animation - Majid al-Rifaie, Mohammad; Ursyn, Anna; Wyeld, Theodor (CRC Press, 2020)
There are countless new apps, methods-related solutions, and web solutions that create opportunities for personal, technological, and materials-related growth, especially when programming for new startups. This book is aimed at making programming easier by presenting it in a visual way. The authors' intention is to help the reader understand the core programming concepts for art, web, and everyday applications including pervasive, ubiquitous, and wearable apps. We also discuss how applying pictures, analogies, and metaphors that refer to familiar sensory faculties helps. Making the programming processes visual helps the reader understand the underlying concepts, and gain the knowledge needed, faster and easier. This book also addresses readings in art, science, mathematics, and other subjects as well as some broader issues such as multicultural, environmental, and social objectives.